2021
DOI: 10.2486/indhealth.2020-0217
|View full text |Cite
|
Sign up to set email alerts
|

Risk of insomnia and hypnotics use among emergency physicians

Abstract: This study investigated the risk of insomnia and hypnotics use among emergency physicians. This cross-sectional study recruited physicians working in Taiwanese hospitals in 2015 and the general population as the participants. Data from 1,097 emergency physicians obtained from the National Health Insurance Research Database were grouped into the case group, whereas 14,112 nonemergency physicians and 4,388 people from the general population were categorized into the control groups. This study used logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Worked more than 40 h a week, with chronic diseases, experienced negative life events, and worked in the emergency department was related with increased insomnia symptoms. These factors have long been recognized as risk factors for insomnia in healthcare workers ( 33 35 ). The relationship between occupational stress and insomnia has long been confirmed ( 11 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Worked more than 40 h a week, with chronic diseases, experienced negative life events, and worked in the emergency department was related with increased insomnia symptoms. These factors have long been recognized as risk factors for insomnia in healthcare workers ( 33 35 ). The relationship between occupational stress and insomnia has long been confirmed ( 11 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…As per the cross-sectional study that was published by Yih-Farng et al evaluating the risk of insomnia and hypnotic use among ED physicians, which enrolled 1,097 ED physicians, 14,112 non-ED physicians, and 4,388 general population in the study, they reported the prevalence of insomnia among ED physicians, non-ED physicians, and the general population to be 5.56%, 4.08%, and 1.73% respectively [19]. Moreover, another survey-based study performed in Japan by Chiba et al that involved 816 ED physicians concluded that the prevalence of chronic insomnia and sleep aid use among ED physicians is approximately 24% [20].…”
Section: Discussionmentioning
confidence: 97%
“…A study based on the Taiwanese National Health Insurance Research Database reported that the prevalence of insomnia was 5.56% and the percentage of hypnotic use was 19.96%. 24 This result was based on International Classification of Diseases codes and the prescription data recorded in the national database; it did not include self-treated insomnia or sleep-aid use without prescription. Therefore, it most likely underestimated the rate of insomnia and sleep-aid use.…”
Section: Discussionmentioning
confidence: 99%